The Influence of Risk Management in Decision Making on Entrepreneurial Success with Product Promotion as a Moderating Variable - Formaida Tambunan; Mery Lani Br Purba; Marupa Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to determine the effect of risk management in decision making on entrepreneurial success with promotions as a moderating variable. The problem in this study is focused on entrepreneurs who often experience failure in entrepreneurship due to inability to apply risk management in entrepreneurship and lack of promotion to the community so that to understand these problems several supporting theories are used, namely risk management, promotion and entrepreneurial success which are also supported by several studies. from existing journals. This type of research is a quantitative associative research with the population being all entrepreneurs with a minimum asset of Rp. 100 million in the area of Central Helvetia Village, Medan Helvetia District, Medan City, There are 153 entrepreneurs in North Sumatra Province and the determination of the number of samples is based on the Slovin formula so that there are 60 respondents with a simple random sampling technique. The data were obtained using a research instrument in the form of a questionnaire and the data analysis used was simple regression and MRA. The results showed that: 1) there is an effect of risk management on entrepreneurial success, 2) Risk management has an effect on entrepreneurial success which is strengthened through product promotion. The data were obtained using a research instrument in the form of a questionnaire and the data analysis used was simple regression and MRA. The results showed that: 1) there is an effect of risk management on entrepreneurial success, 2) Risk management has an effect on entrepreneurial success which is strengthened through product promotion. The data were obtained using a research instrument in the form of a questionnaire and the data analysis used was simple regression and MRA. The results showed that: 1) there is an effect of risk management on entrepreneurial success, 2) Risk management has an effect on entrepreneurial success which is strengthened through product promotion.